I Am Not Alone!: Peer Support as a Pathway to Strengthen Communication among Introverted Students - Canggih Yulia Sakti; Abd. Madjid; Muhammad Buya Al Madany Abror (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2026)
This study investigates how peer relationships contribute to the development of interpersonal communication skills among introverted students in the Islamic Religious Education Study Program at Universitas Muhammadiyah Yogyakarta. Using a qualitative phenomenological design, 10 introverted students were selected through personality screening and interviews. Data were gathered through in-depth interviews and participant observations, then analyzed using the Miles and Huberman model to capture patterns and meanings from their lived experiences. The findings reveal three central themes. First, introverted students tend to demonstrate reflective, thoughtful communication styles, yet they encounter difficulties with nonverbal cues, such as eye contact and body language, which often hinder effective interaction. Second, peer relationships serve as a crucial source of emotional support, providing safe spaces that reduce anxiety and encourage more open dialogue, thereby facilitating gradual improvement in communication competence. Third, both internal factors, including self-confidence and communication anxiety, and external factors, such as the campus environment and opportunities for collaboration, significantly shape their development of interpersonal communication. Overall, the study concludes that peer support plays a vital role in enhancing the confidence, active participation, and communicative competence of introvert students. These insights highlight the need for peer-based strategies and inclusive educational practices in Islamic higher education to better support introvert learners and foster more effective interpersonal engagement.